Fabrication of porous pure titanium via selective laser melting under low-energy-density process conditions. (October 2020) - Kim, Won Rae; Bang, Gyung Bae; Kwon, Ohyung; Jung, Kyung-Hwan; Park, Hyung-Ki; Kim, Gun-Hee; Jeong, Hyo-Tae; Kim, Hyung Giun
Abstract: By controlling specific process conditions in the selective laser melting (SLM) of commercially pure Ti powder (Grade 1), a porous structure was fabricated to achieve a high specific surface area. Additive manufacturing was employed through SLM to control the energy density to be lower than that required for the complete melting of Ti powders by operating at a power of 80 to 480 W and a scan speed of 1750 to 10, 500 mm/s. The range of the process conditions, i.e., complete melting, partial melting, and unmelted, was determined based on the observations of the microstructure parallel to the building direction. When the powders were pre-sintered and not melted under specific process conditions with an energy density lower than that required for complete melting, porous microstructures were formed with open pores. In addition, interfacial microstructural studies were conducted to confirm the presence of residual powder, which settled onto the strut, resulting in a higher specific surface area. These indicate that the SLM process can enhance the porosity, even with a specific design of lattice structures, as fluidic materials are expected to flow through the open porous structure. Graphical abstract: Unlabelled Image Highlights: Process design of SLM for porous CP-Ti having unique microstructure could increase specific surface area Microstructural study on CP-Ti with SLM process conditions lower than completely melting energy density Evaluation on interfacial microstructure of pre-sintered powder on strut and 3D structure